2014
DOI: 10.1007/s13277-014-2274-5
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-AC130710 targeting by miR-129-5p is upregulated in gastric cancer and associates with poor prognosis

Abstract: Long noncoding RNAs (lncRNAs) play an important role in cancer occurrence and development. However, there is largely unknown about lncRNAs significance in the diagnosis and treatment of gastric cancer. In our study, we focused on AC130710, one of lncRNAs. Gastric cancer tissues and adjacent tissues were gathered from 78 patients with gastric cancer. The AC130710 levels were detected by reverse transcription polymerase chain reaction (RT-PCR). Then, we further analyzed the association between AC130710 level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 21 publications
(24 reference statements)
4
74
0
Order By: Relevance
“…When using cell lines as models, we further found that GACAT2 was significantly downregulated in five gastric cancer cell lines (AGS, BGC-823, HGC-27, MGC-803, and SGC-7901) compared with normal gastric epithelial cell GES-1 [2]. Similar to the situations in cell lines, by expanding the gastric cancer sample size (313 samples), we found that GACAT2 was downregulated in 62.6 % gastric cancer tissues compared to the paired adjacent normal tissues [2]. It also significantly decreased in dysplasia compared with healthy control group.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…When using cell lines as models, we further found that GACAT2 was significantly downregulated in five gastric cancer cell lines (AGS, BGC-823, HGC-27, MGC-803, and SGC-7901) compared with normal gastric epithelial cell GES-1 [2]. Similar to the situations in cell lines, by expanding the gastric cancer sample size (313 samples), we found that GACAT2 was downregulated in 62.6 % gastric cancer tissues compared to the paired adjacent normal tissues [2]. It also significantly decreased in dysplasia compared with healthy control group.…”
mentioning
confidence: 89%
“…Shortly after the articles entitled "Low expression of lncRNAHMlincRNA717 in human gastric cancer and its clinical significances" and "lncRNA-AC130710 targeting by miR-129-5p is upregulated in gastric cancer and associates with poor prognosis" published in Tumour Biology [1,2], the long noncoding RNA (lncRNA) HMlincRNA717 and AC130710 that were studied in these papers have been officially named by HUGO Gene Nomenclature Committee (HGNC). Human Gene Nomenclature Database (www.genenames.org/hgncsearches) shows that their HGNC ID is 50516 and 50847, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of miRNAs have been identified to be expressed at low levels in tumors, acting as oncogenes, antioncogene, or regulators of cancer stem cells and metastasis [19]. Reduced expression of miR-129 has been found in multiple tumor cell lines and in primary tumors, including GC [7,14,20]. yu and co-workers [7] suggested that all miR-129 family members (miR-129-1-3p, miR-129-2-3p, and miR-129-5p) showed growth inhibitory in GC by regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports [7,8,14], we investigated the expression pattern of miR-129-5p in GC tissues and peripheral blood samples. In addition, the effect of miR-129-5p on GC cell proliferation, migration, and invasion were explored by altering the endogenous levels of miR-129-5p in human GC cell line SGC-7901 cells.…”
mentioning
confidence: 99%